Rate of convergence of binomial formula for option pricing. Issue 14 (17th July 2020) - Ratibenyakool, Yuttana; Neammanee, Kritsana
Abstract: The Binomial and Black–Scholes formulas are tools for valuating a call option at any specified time. We have already known that the Binomial formula converges to the Black–Scholes formula as the number of periods ( n ) converges to infinity. This research obtains the rate of this convergence, namely 1 n n . Our rate of convergence is better than those obtained by Cox, Ross, and Rubinstein (1979 ), Leisen and Reimer (1996 ), Heston and Zhon (2000), Diener and Diener (2004 ) and Chang and Palmer (2007 ). We also provide the explicit constant of the bound of this convergence.